Gene therapy: A Revolution in Medicine or a Risky Game with our DNA? - Julia Kozakiewicz; Aleksandra Okońska; Kamil Kościelecki; Agnieszka Kalisz; Iwona Skorulska; Klaudia Mączewska; Patrycja Długozima; Paulina Grzeszczuk; Weronika Grywińska; Aleksandra Głowacka (Quality in Sport)
Introduction: The aim of this review is to provide an overview of the applications of gene therapies in various diseases and to highlight areas where further research is needed.